5.1.18 Problems 1701 to 1800

Table 5.35: First order ode

#

ODE

Mathematica

Maple

4616

\[ {}y^{\prime } = x \left ({\mathrm e}^{-x^{2}}+a y\right ) \]

4617

\[ {}y^{\prime } = x^{2} \left (a \,x^{3}+b y\right ) \]

4618

\[ {}y^{\prime } = a \,x^{n} y \]

4619

\[ {}y^{\prime } = \sin \left (x \right ) \cos \left (x \right )+y \cos \left (x \right ) \]

4620

\[ {}y^{\prime } = {\mathrm e}^{\sin \left (x \right )}+y \cos \left (x \right ) \]

4621

\[ {}y^{\prime } = y \cot \left (x \right ) \]

4622

\[ {}y^{\prime } = 1-y \cot \left (x \right ) \]

4623

\[ {}y^{\prime } = x \csc \left (x \right )-y \cot \left (x \right ) \]

4624

\[ {}y^{\prime } = \left (2 \csc \left (2 x \right )+\cot \left (x \right )\right ) y \]

4625

\[ {}y^{\prime } = \sec \left (x \right )-y \cot \left (x \right ) \]

4626

\[ {}y^{\prime } = {\mathrm e}^{x} \sin \left (x \right )+y \cot \left (x \right ) \]

4627

\[ {}y^{\prime }+\csc \left (x \right )+2 y \cot \left (x \right ) = 0 \]

4628

\[ {}y^{\prime } = 4 \csc \left (x \right ) x \sec \left (x \right )^{2}-2 y \cot \left (2 x \right ) \]

4629

\[ {}y^{\prime } = 2 \cot \left (x \right )^{2} \cos \left (2 x \right )-2 y \csc \left (2 x \right ) \]

4630

\[ {}y^{\prime } = 4 \csc \left (x \right ) x \left (\sin \left (x \right )^{3}+y\right ) \]

4631

\[ {}y^{\prime } = 4 \csc \left (x \right ) x \left (1-\tan \left (x \right )^{2}+y\right ) \]

4632

\[ {}y^{\prime } = y \sec \left (x \right ) \]

4633

\[ {}y^{\prime }+\tan \left (x \right ) = \left (1-y\right ) \sec \left (x \right ) \]

4634

\[ {}y^{\prime } = y \tan \left (x \right ) \]

4635

\[ {}y^{\prime } = \cos \left (x \right )+y \tan \left (x \right ) \]

4636

\[ {}y^{\prime } = \cos \left (x \right )-y \tan \left (x \right ) \]

4637

\[ {}y^{\prime } = \sec \left (x \right )-y \tan \left (x \right ) \]

4638

\[ {}y^{\prime } = \sin \left (2 x \right )+y \tan \left (x \right ) \]

4639

\[ {}y^{\prime } = \sin \left (2 x \right )-y \tan \left (x \right ) \]

4640

\[ {}y^{\prime } = \sin \left (x \right )+2 y \tan \left (x \right ) \]

4641

\[ {}y^{\prime } = 2+2 \sec \left (2 x \right )+2 y \tan \left (2 x \right ) \]

4642

\[ {}y^{\prime } = \csc \left (x \right )+3 y \tan \left (x \right ) \]

4643

\[ {}y^{\prime } = \left (a +\cos \left (\ln \left (x \right )\right )+\sin \left (\ln \left (x \right )\right )\right ) y \]

4644

\[ {}y^{\prime } = 6 \,{\mathrm e}^{2 x}-y \tanh \left (x \right ) \]

4645

\[ {}y^{\prime } = f \left (x \right ) f^{\prime }\left (x \right )+f^{\prime }\left (x \right ) y \]

4646

\[ {}y^{\prime } = f \left (x \right )+g \left (x \right ) y \]

4647

\[ {}y^{\prime } = x^{2}-y^{2} \]

4648

\[ {}y^{\prime }+f \left (x \right )^{2} = f^{\prime }\left (x \right )+y^{2} \]

4649

\[ {}y^{\prime }+1-x = y \left (x +y\right ) \]

4650

\[ {}y^{\prime } = \left (x +y\right )^{2} \]

4651

\[ {}y^{\prime } = \left (x -y\right )^{2} \]

4652

\[ {}y^{\prime } = 3-3 x +3 y+\left (x -y\right )^{2} \]

4653

\[ {}y^{\prime } = 2 x -\left (x^{2}+1\right ) y+y^{2} \]

4654

\[ {}y^{\prime } = x \left (x^{3}+2\right )-\left (2 x^{2}-y\right ) y \]

4655

\[ {}y^{\prime } = 1+x \left (-x^{3}+2\right )+\left (2 x^{2}-y\right ) y \]

4656

\[ {}y^{\prime } = \cos \left (x \right )-\left (\sin \left (x \right )-y\right ) y \]

4657

\[ {}y^{\prime } = \cos \left (2 x \right )+\left (\sin \left (2 x \right )+y\right ) y \]

4658

\[ {}y^{\prime } = f \left (x \right )+x f \left (x \right ) y+y^{2} \]

4659

\[ {}y^{\prime } = \left (3+x -4 y\right )^{2} \]

4660

\[ {}y^{\prime } = \left (1+4 x +9 y\right )^{2} \]

4661

\[ {}y^{\prime } = 3 a +3 b x +3 b y^{2} \]

4662

\[ {}y^{\prime } = a +b y^{2} \]

4663

\[ {}y^{\prime } = a x +b y^{2} \]

4664

\[ {}y^{\prime } = a +b x +c y^{2} \]

4665

\[ {}y^{\prime } = a \,x^{n -1}+b \,x^{2 n}+c y^{2} \]

4666

\[ {}y^{\prime } = a \,x^{2}+b y^{2} \]

4667

\[ {}y^{\prime } = \operatorname {a0} +\operatorname {a1} y+\operatorname {a2} y^{2} \]

4668

\[ {}y^{\prime } = f \left (x \right )+a y+b y^{2} \]

4669

\[ {}y^{\prime } = 1+a \left (x -y\right ) y \]

4670

\[ {}y^{\prime } = f \left (x \right )+g \left (x \right ) y+y^{2} a \]

4671

\[ {}y^{\prime } = x y \left (3+y\right ) \]

4672

\[ {}y^{\prime } = 1-x -x^{3}+\left (2 x^{2}+1\right ) y-x y^{2} \]

4673

\[ {}y^{\prime } = x \left (2+x^{2} y-y^{2}\right ) \]

4674

\[ {}y^{\prime } = x +\left (1-2 x \right ) y-\left (1-x \right ) y^{2} \]

4675

\[ {}y^{\prime } = a x y^{2} \]

4676

\[ {}y^{\prime } = x^{n} \left (a +b y^{2}\right ) \]

4677

\[ {}y^{\prime } = a \,x^{m}+b \,x^{n} y^{2} \]

4678

\[ {}y^{\prime } = \left (a +b y \cos \left (k x \right )\right ) y \]

4679

\[ {}y^{\prime } = \sin \left (x \right ) \left (2 \sec \left (x \right )^{2}-y\right ) \]

4680

\[ {}y^{\prime }+4 \csc \left (x \right ) = \left (3-\cot \left (x \right )\right ) y+y^{2} \sin \left (x \right ) \]

4681

\[ {}y^{\prime } = y \sec \left (x \right )+\left (-1+\sin \left (x \right )\right )^{2} \]

4682

\[ {}y^{\prime }+\tan \left (x \right ) \left (1-y^{2}\right ) = 0 \]

4683

\[ {}y^{\prime } = f \left (x \right )+g \left (x \right ) y+h \left (x \right ) y^{2} \]

4684

\[ {}y^{\prime } = \left (a +b y+c y^{2}\right ) f \left (x \right ) \]

4685

\[ {}y^{\prime }+\left (a x +y\right ) y^{2} = 0 \]

4686

\[ {}y^{\prime } = \left (a \,{\mathrm e}^{x}+y\right ) y^{2} \]

4687

\[ {}y^{\prime }+3 a \left (y+2 x \right ) y^{2} = 0 \]

4688

\[ {}y^{\prime } = y \left (a +b y^{2}\right ) \]

4689

\[ {}y^{\prime } = \operatorname {a0} +\operatorname {a1} y+\operatorname {a2} y^{2}+\operatorname {a3} y^{3} \]

4690

\[ {}y^{\prime } = x y^{3} \]

4691

\[ {}y^{\prime }+y \left (1-x y^{2}\right ) = 0 \]

4692

\[ {}y^{\prime } = \left (a +b x y\right ) y^{2} \]

4693

\[ {}y^{\prime }+2 x y \left (1+a x y^{2}\right ) = 0 \]

4694

\[ {}y^{\prime }+\left (\tan \left (x \right )+y^{2} \sec \left (x \right )\right ) y = 0 \]

4695

\[ {}y^{\prime }+y^{3} \sec \left (x \right ) \tan \left (x \right ) = 0 \]

4696

\[ {}y^{\prime } = \operatorname {f0} \left (x \right )+\operatorname {f1} \left (x \right ) y+\operatorname {f2} \left (x \right ) y^{2}+\operatorname {f3} \left (x \right ) y^{3} \]

4697

\[ {}y^{\prime } = a \,x^{\frac {n}{1-n}}+b y^{n} \]

4698

\[ {}y^{\prime } = f \left (x \right ) y+g \left (x \right ) y^{k} \]

4699

\[ {}y^{\prime } = f \left (x \right )+g \left (x \right ) y+h \left (x \right ) y^{n} \]

4700

\[ {}y^{\prime } = \sqrt {{| y|}} \]

4701

\[ {}y^{\prime } = a +b y+\sqrt {\operatorname {A0} +\operatorname {B0} y} \]

4702

\[ {}y^{\prime } = a x +b \sqrt {y} \]

4703

\[ {}y^{\prime }+x^{3} = x \sqrt {x^{4}+4 y} \]

4704

\[ {}y^{\prime }+2 y \left (1-x \sqrt {y}\right ) = 0 \]

4705

\[ {}y^{\prime } = \sqrt {a +b y^{2}} \]

4706

\[ {}y^{\prime } = y \sqrt {a +b y} \]

4707

\[ {}y^{\prime }+\left (f \left (x \right )-y\right ) g \left (x \right ) \sqrt {\left (y-a \right ) \left (y-b \right )} = 0 \]

4708

\[ {}y^{\prime } = \sqrt {X Y} \]

4709

\[ {}y^{\prime } = \cos \left (x \right )^{2} \cos \left (y\right ) \]

4710

\[ {}y^{\prime } = \sec \left (x \right )^{2} \cot \left (y\right ) \cos \left (y\right ) \]

4711

\[ {}y^{\prime } = a +b \cos \left (A x +B y\right ) \]

4712

\[ {}y^{\prime }+f \left (x \right )+g \left (x \right ) \sin \left (a y\right )+h \left (x \right ) \cos \left (a y\right ) = 0 \]

4713

\[ {}y^{\prime } = a +b \cos \left (y\right ) \]

4714

\[ {}y^{\prime }+x \left (\sin \left (2 y\right )-x^{2} \cos \left (y\right )^{2}\right ) = 0 \]

4715

\[ {}y^{\prime }+\tan \left (x \right ) \sec \left (x \right ) \cos \left (y\right )^{2} = 0 \]